Knowledge Game for Improvement Engineering Visual Inspection - Mana Patamakajonpong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Operation and maintenance of the utility’s assets are regarded as an integral part in the Asset Management activities. Hence, in order to perform these tasks effectively, relevant knowledge and skills are required, especially the one associating with the visual inspection. This visual inspection skill is very important since it allows the maintenance operator to be able to observe and make appropriate decisions on maintenance activities according to asset’s conditions. Due to its heavily reliance on encountering with the asset, this type of knowledge and skill is classified as episodic where being in the real environment is needed in order to acquire this knowledge. However, the traditional training methods, including both classroom and e-Learning, take no consideration of the specific nature of this type of knowledge and skill. As a result, it proves to be less effective to enhance the visual inspection skills of the maintenance operator. This research develops and proposes an alternative method for the development of the visual inspection skills of the maintenance staff. The knowledge game development framework is proposed to construct the scenarios. The scenario selection engine is also considered and included in this research to present maintenance operator with a set of challenging scenarios. The results have shown that scenarios can be systematically constructed and provide flexibility for future modification. The results also presents that the game based knowledge management method shows better outcomes comparing to the traditional training methods. Moreover, the results have shown that the proposed framework can be utilized to identify the capability level of the individual trainee. Furthermore, the appropriate maturity development of the employees in each level can also be identified. This proposed framework provides better results when comparing to the current PEA competency model since the criteria in this framework is systematically derived from experts rather than relying solely on the proficiency level. In this research, the 22 kV Switchgear Maintenance task of Provincial Electricity Authority in Thailand is used as the case study.